THE EFFECT OF WHEATGRASS JUICE ON HEMOGLOBIN LEVEL W.S.R. TO SAMANYA-VISHESHA SIDDHANTA - Kiran Bhikaji, Pawar; Mangala P, Thakare; Sudhakar, Meshram Dnyaneshwar; Manju Namdev, Jadhao (International Journal of Ayurveda and Pharma Research, 2015)
W.H.O. guideline denotes hemoglobin level in healthy male below 13 g/dl is abnormal and in female below 12g/dl is abnormal. This condition refers as Anaemia. There are several types of anaemia. It develops mainly because of lack of proper food habits. Wheat grass juice is rich source of minerals, vitamins, antioxidants, amino acids and many enzymes. It is significant nutritious and medicinal value with rich source of chlorophyll. Chlorophyll resembles with hemoglobin as both are chromo protein. Chemical component of both compounds are nearly same. Also the vital component of wheat grass helps in building hemoglobin in our body. The presence of 70% chlorophyll, which is almost chemically identical to hemoglobin. The only difference is that the central element in chlorophyll is magnesium and in hemoglobin it is iron. Chlorophyll in wheat grass is more useful in various clinical conditions involving hemoglobin deficiency and other chronic disorders ultimately considered as green blood. This study aims to evaluate the effect of wheatgrass fresh juice on hemoglobin level. Here 30 subjects were selected in the study and divided into 3 groups on basis of their hemoglobin level. Group A having Hb%, 13gm% to 16gm%, group B having Hb% 10gm% to 13gm% and group C having Hb% below 10gm%. After 21 days the symptomatic improvement and increase in hemoglobin level in group C was noticed as compared to group A and group B. No significant therapy is there for chronic anaemias in modern science. So an attempt has been made to evaluate the efficacy of wheat grass juice on hemoglobin level in the subjects having normal as well as abnormal hemoglobin level.